Roman Numerals in Teaching and Grammar and Orthography Handbooks of the Serbian Language - Goran N. Zeljić; Ljubica D. Vesić (University of Belgrade, Teacher Education Faculty, 2019)
The orthographic norm specifies that Roman numerals (numbers) are used to denote ordinal numbers and represent a semantic equivalent to Arabic numerals with a full-stop, or ordinal numbers, as a numerical type, and therefore, with Roman numerals, the full-stop is not written (for example, XLVI FEST = 46 FEST). Bearing this in mind, the authors highlighted the importance of Roman numerals in the system of numerical types in the relevant orthography and grammar handbooks (from Belić's and Matica's orthography handbooks to Normative Grammar) and offered solutions that would regulate their normative status and place in the orthography and grammar of the Serbian Language. The paper analyzes the results obtained from the candidates at the entrance exam at the Teacher Education Faculty in Belgrade in 2017 on the tasks related to the knowledge of Roman numerals. The sample consisted of 405 candidates from both departments. The results of the research show that the knowledge that students acquire in the instruction of orthography is insufficient to clearly distinguish the functional marking of Roman numerals (on one hand, as linguistic, and on the other, as mathematical symbols). The results indicate the need for a systematic processing of Roman numerals within ordinal numbers (as one of the alternative solutions for their expression, in addition to the numerical word and Arabic numerals with a full-stop).